Knowledge Management Practices in the Institutions of Higher Learning in Kenya, Issues and Opportunities a Case Study of University of Eldoret - Lelon , Lydia (African Journal of Education,Science and Technology (AJEST), 2017)
Today we live in a global world where technology is seen as the blood of every livelihood. Innovations are invented every day. Information or knowledge needs to be accessed and utilized. Effects of knowledge transfer and diffusion needs to be felt in every aspect of research and development in the institutions of higher learning in Kenya. Universities spend millions of money in creating Knowledge either out of their daily operations or academic programs. The knowledge produced is stored and disseminated in digital or printed format. Very few of this knowledge find their way to be published into journal articles or shared among peers. This has created challenge to the effective -utilization of this explicit knowledge to enhance performance of local universities and gain competitive advantage for better rankings. The objective of this study was to establish the level of practice among the academic staff at the University of Eldoret (UoE) and determine factors that affect knowledge management (KM) practices at individual, school and university level. All the eight schools and the library were sampled for the study and the response rate was 85 % which was a positive response. The study adopted a descriptive research design interview schedules were administered to some members of management, administrative staff and Information service providers, whereas postgraduate students, faculty staff and researchers were given questionnaires. The study found out that knowledge per se was not part of these universities core functions and neither had it been formally introduced and any understanding of KM as a term was from literacy sources. Despite this fact KM practices were rated as good (62.3%) and very good (10.7%) among researchers and faculty staff. The library staff agreed to have had means of identifying and capturing knowledge. These practices were however more for information management than KM. Lack of effective knowledge management practices influenced the state of KM at UoE. The study recommended development of effective knowledge management culture, systems and Info-culture for competitive advantage